1995
DOI: 10.1103/physrevb.51.12009
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘‘Particle-size effects on the value ofTCofMnFe2

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 13 publications
1
28
0
1
Order By: Relevance
“…This disorder has caused some confusion both in the analysis of the dependence of magnetic properties on sample size [4][5][6][7] and in understanding the temperature dependence of transport quantities. 12 There, we found that the electronic structure is highly sensitive to the structural parameters used, particularly, the internal O coordinate u of the spinel structure.…”
mentioning
confidence: 99%
“…This disorder has caused some confusion both in the analysis of the dependence of magnetic properties on sample size [4][5][6][7] and in understanding the temperature dependence of transport quantities. 12 There, we found that the electronic structure is highly sensitive to the structural parameters used, particularly, the internal O coordinate u of the spinel structure.…”
mentioning
confidence: 99%
“…11 However, the strength of exchange interaction for Mn 2+ (A)-Fe 3+ (B) is smaller than that of Fe 3+ (A)-Fe 3+ (B). 5,6,12,13 Hence any change in inversion affects the exchange constant but not the net magnetic moment. 6,11,12 In this paper, we report the magnetic properties of MnFe 2 O 4 thin films pulsed laser deposited (PLD) at various substrate temperatures (T S ).…”
Section: Introductionmentioning
confidence: 99%
“…5,6,12,13 Hence any change in inversion affects the exchange constant but not the net magnetic moment. 6,11,12 In this paper, we report the magnetic properties of MnFe 2 O 4 thin films pulsed laser deposited (PLD) at various substrate temperatures (T S ). We have estimated the value of exchange stiffness constant (D) by fitting the temperature dependence of magnetization data to Bloch's law and determined the effect of deposition temperature on the values of D in thin films and hence on the inversion of these films.…”
Section: Introductionmentioning
confidence: 99%
“…to Mn 3? and different cation distributions of ferrite nanoparticles can decrease the lattice constant [31,32]. Density of the prepared samples was calculated using the Archimedes principle from precise measurements of the dry, saturated and suspended weight.…”
Section: Xrd Analysismentioning
confidence: 99%